2003
DOI: 10.1590/s0034-89102003000500008
|View full text |Cite
|
Sign up to set email alerts
|

Escore CRIB, peso ao nascer e idade gestacional na avaliação do risco de mortalidade neonatal

Abstract: ObjectiveTo evaluate the mortality rate of very low birth weight babies born at a Neonatal Intensive Care Unit (NICU) during a specified period of time according to variations in CRIB (Clinical Risk Index for Babies) score, birth weight and gestational age. MethodsFrom January 1997 to December 2000, the CRIB score was prospectively applied to all newborn infants admitted to the N ICU of an university hospital, of Londrina, Brazil, with birthweight under 1,500 g and/or less than 31 weeks' gestational age. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 15 publications
(12 reference statements)
3
10
0
8
Order By: Relevance
“…(4) In this study, a significant association for very low birth weight -below 1,500 grams, was identified, 57%, in agreement with other studies showing that this group mortality is still very high in Brazil, specially in those below 750 grams (14) and far away from the rate in the best services, with about 10% mortality for very low weight infants. (15) For the Araujo et al (16) study, low birth weight is associated with unfavorable social-economic situation, making the newborn more vulnerable to conditions such as prematurity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…(4) In this study, a significant association for very low birth weight -below 1,500 grams, was identified, 57%, in agreement with other studies showing that this group mortality is still very high in Brazil, specially in those below 750 grams (14) and far away from the rate in the best services, with about 10% mortality for very low weight infants. (15) For the Araujo et al (16) study, low birth weight is associated with unfavorable social-economic situation, making the newborn more vulnerable to conditions such as prematurity.…”
Section: Discussionsupporting
confidence: 90%
“…(14) It was thus possible to identify risk factor associated with death in newborns staying in the Taubaté University Hospital neonatal ICU in the years 2005, 2006 and 2007, being these results comparable to others in literature reported populations. In addition, this model allowed hierarchically understanding the relationship between these factors in the causality of infant mortality, using a still seldom used study frame.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Prematurity is immediate or late manifestations of the growth and development of children [1][2][3] , and the survival of premature infants one of the most important challenges of neonatology 4,5 . New technologies used in the neonatal intensive care led to improvements in the quality of perinatal care of preterm infants resulting in increased survival of newborns with morbidities such as perinatal asphyxia, respiratory distress syndrome (RDS), hemorrhage periintraventricular (HPIV) infections and necrotizing enterocolitis 6 .…”
Section: Introductionmentioning
confidence: 99%
“…(12) . Porém, vários estudos revelam haver um aumento nas taxas de morbimortalidade e atrasos no desenvolvimento neurocomportamental em RNs prematuros e com baixos pesos ao nascer, sendo essa relação inversamente proporcional, ou seja, quanto menores a idade gestacional e o peso ao nascer maiores são as complicações (11)(12)(13) . Outro aspecto relevante sobre a condição do RN ao nascer é escore obtido pelos bebês no Boletim de Apgar.…”
Section: Aspiração Orunclassified